Generic Structure of Tourism Promotion Website of Madura Natural Wonders - Ekawati, Rosyida; Puspitasari, Desi (Lingua Cultura, 2019)
The research examined a genre-based analysis of a tourism promotion website of natural wonders on the official website of Sumenep regency. It used descriptive qualitative research. Source of the data was the Indonesian website of Sumenep regency on five natural wonders: they were tourism destinations in Gili Iyang, Gili Labak, Pantai Badur, Pantai Lombang, and Pantai Slopeng. Data collection was done by a classification of the move, step, and strategy that was proposed by Huang on sentence-based using Nvivo software. The findings yield from the proposed move and steps, and there are only four moves available compared to the proposed move and step. They comprise the move 1 headline, move 2 establishing credentials, move 3 directive information, move 4 soliciting response, and four steps in move 2 comprises step 1 introducing general situation, step 2 quoting literature, step 3 describing services or facilities, and step 4 describing critical attractions in the tourism promotion official website. The four moves found in official websites become obligatory because all moves are available in all contents of the tourism promotion website. The establishing credential move occupies the large portion of the website in giving information about the destination. Move 2 steps 2 quoting literature and move four could be categorized into non-obligatory moves because of those moves only available in one of the tourism promotions in the official website of Sumenep regency.